Fusarium species associated with wheat head blight disease in Algeria: characterization and effects of triazole fungicides: Behaviour of Fusarium head blight to triazole - Imane, Belabed; Hannane, Abed; Amor, Bencheikh; Noureddine, ROUAG (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Fusarium head blight is an important disease of durum wheat which requires several fungicide treatments of seeds to achieve satisfactory control. The current study was carried out to evaluate commercially available fungicides in vitro for their efficacy against eighteen Fusarium spp. isolates collected from different fields in the north-eastern part of Algeria. The morphological and molecular characterization reveals the presence in wheat seeds of the main species complexes F. acuminatum, F. equiseti, F. avenaceum, F. solani, F. culomorum, F. incarnatum-equiseti, as well as F. tricinctum species complex and F. chlamydosporum species complex. Antifungal activity of fungicides shows that all triazoles tested have proven their effectiveness in inhibiting the mycelial growth of various strains of Fusarium tested. However, their sensitivity varies between them significantly (p
Keywords: wheat; Fusarium; fungicides; toxicity